Glass, optical filter and optical device

By optimizing the composition and structure of the ytterbium-containing glass, it ensures that it has excellent absorption characteristics in the near-infrared region, solving the problem of insufficient absorption in the prior art, and achieving efficient light absorption effect under miniaturization and thinning conditions.

CN119403770APending Publication Date: 2025-02-07AGC INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380048433.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-29
Filing Date
2023-06-23
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The lack of absorption of bbl-containing glass in the near-infrared region described in the prior art leads to the need to increase the glass thickness to obtain sufficient absorption. However, in recent years, the miniaturization and thinning of the camera module have made installation difficult.

Method used

A glass containing ytterbium (Yb) was developed, which had a transmittance of light with a wavelength of 940 nm below 30% when converted to a thickness of 0.4 mm. By optimizing the composition and structure of the glass, it ensured excellent absorption characteristics in the near infrared region.

Benefits of technology

Even if the thickness is very small, the glass can fully absorb light in the near-infrared region, which solves the problem of insufficient absorption in the prior art, and can reliably cut off long wavelengths with wavelengths greater than 850 nm without affecting the light transmission characteristics of wavelengths of 850 nm. Unwanted light on the side.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403770A_ABST
    Figure CN119403770A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a glass containing ytterbium (Yb) and having excellent absorption characteristics in the near-infrared region. The present invention relates to a glass containing ytterbium and having a transmittance of 30% or less for light having a wavelength of 940 nm when converted to a thickness of 0.4 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to ytterbium-containing glass, and an optical filter and an optical device having the glass. Background Art

[0002] The use of imaging devices using solid-state imaging elements is expanding to devices that capture images day and night, such as surveillance cameras and car-mounted cameras. Such devices need to obtain images based on visible light (color) and images based on infrared light (black and white).

[0003] Therefore, the use of an optical filter, namely, a dual-bandpass filter, which has a function of selectively transmitting specific near-infrared light in addition to a near-infrared cut filter function of transmitting visible light and faithfully reproducing an image based on the visible light, is being studied.

[0004] Optical filters have wavelength selectivity by having the function of absorbing specific light and the function of reflecting specific light by changing the refractive index.

[0005] Here, light-absorbing glass is studied as a material having a function of absorbing specific light.

[0006] Patent Document 1 discloses glass containing ytterbium (Yb) and having absorption in the near-infrared region.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: International Publication No. 2016 / 114274 Summary of the invention

[0010] Technical problem to be solved by the invention

[0011] However, the glass described in Patent Document 1 has insufficient absorption in the near-infrared region. In order to obtain sufficient absorption, it is necessary to increase the thickness of the glass, for example, but considering the miniaturization and thinning of camera modules in recent years, it may be difficult to mount them.

[0012] An object of the present invention is to provide glass containing ytterbium (Yb) and having excellent absorption characteristics in the near-infrared region.

[0013] Technical solutions adopted to solve technical problems

[0014] The present invention relates to glass having the following constitution.

[0015] [1] Glass containing ytterbium and having a transmittance of 30% or less for light having a wavelength of 940 nm when converted to a thickness of 0.4 mm.

[0016] Effects of the Invention

[0017] The glass of the present invention contains ytterbium (Yb) and has excellent absorption characteristics in the near-infrared region. Therefore, even if the thickness is small, it can fully absorb light in the near-infrared region. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 3 is a graph showing the spectral transmittance curves of the glasses of Examples 7, 90 and 2. DETAILED DESCRIPTION

[0019] The glass of the present embodiment contains ytterbium in the glass composition, and the transmittance of light having a wavelength of 940 nm is 30% or less when converted to a thickness of 0.4 mm.

[0020] In addition, the incident direction of light during measurement refers to the normal direction with respect to the main surface, that is, the incident angle is 0 degrees.

[0021] In addition, the transmittance of the glass converted to a thickness of 0.4 mm is obtained by converting the transmittance of the glass sample of a specified thickness into the transmittance when the thickness is 0.4 mm using the following formula (1) based on the measured transmittance of the glass sample, assuming that the reflectance of the front and rear surfaces of the glass is 8.12% respectively. In formula (1), R is 0.0812 based on the above reflectance.

[0022] Converted transmittance (thickness 0.4mm) = 100 × (1-R) 2 ×{Measured transmittance (0deg) / (100×(1-R) 2 )} (0.4 / 实测厚度) …Formula (1)

[0023] For example, in a sensor that uses light with a wavelength of 850 nm, it is necessary to reliably cut off light outside the wavelength range of 50 to 100 nm centered on the wavelength of 850 nm. As a method of cutting off light of a specific wavelength, an optical filter that uses the reflection characteristics of a dielectric multilayer film is known. However, as the incident angle of light relative to the filter increases, the reflection characteristics of the dielectric multilayer film shift toward the short wavelength side, and this shift in the reflection characteristics depending on the incident angle becomes more obvious in the long wavelength region. Therefore, the transmission characteristics of light with a wavelength of 850 nm may be adversely affected.

[0024] In contrast, ytterbium-containing glass particularly absorbs near-infrared light in the 900-1000nm wavelength range. In addition, since the absorption band is steep, it is possible to maintain high transmittance in areas other than the maximum absorption wavelength region, and has excellent transmittance in the visible light region and the near-infrared light region from visible light to about 800nm. In addition, since the absorption characteristics are used to cut off light, unlike dielectric multilayer films, the spectral characteristics are less affected by the incident angle.

[0025] The glass of this embodiment has the above-mentioned spectral characteristics, so in the optical filter installed in the sensor using the light of wavelength 850nm, it is possible to reliably cut off the unnecessary light of the long wavelength side of wavelength greater than 850nm without affecting the transmission characteristics of the light of wavelength 850nm. In addition, when the glass of this embodiment and the dielectric multilayer film are used together, the number of film layers of the dielectric multilayer film can also be reduced. In addition, the present invention is not limited to the sensor using the light of wavelength 850nm, and can also be used for the optical filter with small change of spectral characteristics caused by the incident angle of light in the use of cutting off the light of wavelength around 940nm.

[0026] The glass of the present embodiment preferably has a transmittance of light of a wavelength of 940 nm when converted to a thickness of 0.4 mm, of 25% or less, more preferably 15% or less, further preferably 10% or less, particularly preferably 8% or less, and most preferably 6% or less.

[0027] In addition, the transmittance of the glass of this embodiment at a wavelength of 850 nm when converted to a thickness of 0.4 mm is preferably 78% or more, more preferably 79% or more, further preferably 80% or more, further preferably 81% or more, particularly preferably 82% or more, and most preferably 83% or more.

[0028] In the glass of the present embodiment, when the thickness is converted to 0.4 mm, the wavelength on the long wavelength side among the wavelengths in the wavelength range of 800 to 1100 nm at which the transmittance is 50% is denoted as λ. IRL50 , set the wavelength on the short wavelength side to λ IRS50 When IRL50 With λ IRS50 The absolute value of the difference Δλ IR50 It is preferably 100 to 160 nm.

[0029] The glass of this embodiment has this spectral characteristic, so the light transmittance changes sharply from a wavelength of 850nm to a wavelength of 940nm (the slope of the relationship between wavelength and transmittance is large). Therefore, for example, when used as a filter for a solid-state imaging element that senses light with a wavelength of 850nm, it is possible to maintain a high degree of shielding against light around a wavelength of 940nm that becomes noise, while increasing the light transmittance at a wavelength of 850nm, thereby improving the sensing accuracy.

[0030] Δλ IR50 The diameter is more preferably 105 nm or more, and further preferably 110 nm or more. Furthermore, the diameter is more preferably 155 nm or less, and further preferably 150 nm or less.

[0031] The glass of this embodiment preferably has a transmittance of 80% or more for light of 400 nm wavelength when converted to a thickness of 0.4 mm. Since the glass of this embodiment has such spectral characteristics, when used as a filter for a solid-state imaging element that uses visible light for imaging, an image with good color reproducibility can be obtained.

[0032] The transmittance of the glass of this embodiment at a wavelength of 400 nm when converted to a thickness of 0.4 mm is more preferably 81% or more, further preferably 82% or more, further preferably 83% or more, particularly preferably 83.5% or more, and most preferably 84% or more.

[0033] The Young's modulus of the glass of the present embodiment is preferably 100 to 150 GPa. Young's modulus is a physical property that serves as an index of the strength and hardness of glass. If the Young's modulus is above 100 GPa, the strength and hardness of the glass are sufficiently high. For example, when used as a filter for a solid-state imaging element, deformation of the glass and damage to the optical filter due to the impact when the imaging device falls can be avoided. In addition, if the Young's modulus is below 150 GPa, the glass is easy to process and is not prone to problems such as rising costs during glass manufacturing.

[0034] Hereinafter, each component that can constitute the glass of the present embodiment and its suitable content (expressed in mol % based on oxides) will be described. In this specification, unless otherwise specified, the content and total content of each component are expressed in mol % based on oxides.

[0035] Yb2O3 is an essential component for effectively absorbing light with a wavelength of 900 to 1000 nm, especially light with a wavelength of 940 nm, and reducing transmittance. In the glass of this embodiment, if the content of Yb2O3 is 20% or more, this effect can be fully obtained, and if it is 60% or less, it is not easy to cause problems such as devitrification of the glass, deterioration of melting properties, and generation of stray light due to fluorescence.

[0036] Therefore, the content of Yb2O3 is preferably 20-60%, more preferably 25-60%, further preferably 30-60%, further preferably 35-60%, particularly preferably greater than 40% and less than 60%, and most preferably 45% to 60%.

[0037] SiO2 is a main component of glass and is used to improve the resistance to devitrification and the viscosity of glass relative to the liquidus temperature. If the content of SiO2 in the glass of this embodiment is 0.1% or more, it is not easy to cause problems such as the glass becoming unstable, the weather resistance being reduced, and the generation of wave streaks in the glass. If the content of SiO2 is less than 50%, it is not easy to cause problems such as the deterioration of the melting property of the glass.

[0038] Therefore, the SiO2 content is preferably 0.1-50%, more preferably 0.1-40%, further preferably 0.1-30%, further preferably 0.1%-20%, particularly preferably 0.1-10%, and most preferably above 0.1% and less than 3%.

[0039] B2O3 is a main component of glass and is used to improve the resistance to devitrification and the viscosity of glass relative to the liquidus temperature. If the content of B2O3 in the glass of this embodiment is 15% or more, the glass is less likely to become unstable. If the content of B2O3 is 40% or less, the weather resistance of the glass is less likely to decrease, and wave streaks are less likely to occur.

[0040] Therefore, the content of B2O3 is preferably 15 to 40%, more preferably 15 to 38%, further preferably 15 to 36%, further preferably 15 to 34%, particularly preferably 15 to 32%, and most preferably 15 to 32%.

[0041] From the viewpoint of obtaining stable glass, the glass of the present embodiment preferably contains at least one of SiO2 and B2O3. From the viewpoint of preventing the glass from becoming unstable, the total content of the above components is preferably greater than 65%. Furthermore, from the viewpoint of preventing the glass from becoming less fusible, the total content of the above components is preferably less than 80%.

[0042] Therefore, it is more preferably greater than 65% and less than 79%, further preferably greater than 65% and less than 78%, further preferably greater than 65% and less than 77%, particularly preferably greater than 65% and less than 76%, and most preferably greater than 65% and less than 75%.

[0043] P2O5 is a component used to improve the melting property and stability of glass. In the glass of this embodiment, the content of P2O5 is preferably 0 to 15%. If the content of P2O5 is below 15%, it is not easy to cause problems such as deterioration of weather resistance of glass, phase separation of glass, and generation of wave streaks in glass.

[0044] The P2O5 content is more preferably 1 to 13%, further preferably 2 to 12%, further preferably 3 to 11%, and most preferably 4 to 10%.

[0045] GeO2 is a component for improving the resistance to devitrification of glass and the viscosity relative to the liquidus temperature. In the glass of this embodiment, the content of GeO2 is preferably 0 to 15%. If the content of GeO2 is below 15%, it is not easy to cause problems such as poor melting properties of the glass.

[0046] The content of GeO2 is more preferably 0 to 13%, further preferably 0 to 11%, further preferably 0 to 9%, and most preferably 0 to 7%.

[0047] Ga2O3 is a component used to increase the Young's modulus of glass, improve melting properties and stability. In the glass of this embodiment, the content of Ga2O3 is preferably 0 to 30%. If the content of Ga2O3 is below 30%, it is not easy to cause problems such as devitrification of the glass, increase in reflectivity, and generation of stray light due to reflected light.

[0048] The Ga2O3 content is more preferably 0.5 to 28%, further preferably 1 to 26%, further preferably 2 to 24%, and most preferably 3 to 22%.

[0049] ZrO2 is a component for increasing the Young's modulus of glass and the viscosity of glass relative to the liquidus temperature. In the glass of this embodiment, the content of ZrO2 is preferably 0 to 7%. If the content of ZrO2 is below 7%, it is not easy to cause problems such as devitrification and melting of the glass.

[0050] The ZrO2 content is more preferably 0 to 6%, further preferably 0 to 5%, further preferably 0 to 4%, and most preferably 0 to 3%.

[0051] La2O3 is a component used to increase the Young's modulus of glass and improve its melting property. In the glass of this embodiment, the content of La2O3 is preferably 0.1 to 20%. If the content of La2O3 is 0.1% or more, its effect can be fully obtained. If it is less than 20%, it is not easy to cause problems such as devitrification of the glass, increase in reflectivity, and generation of stray light due to reflected light.

[0052] The La2O3 content is more preferably 0.5 to 19%, further preferably 1 to 18%, further preferably 2 to 17%, and most preferably 2 to 16%.

[0053] Al2O3 is a component used to increase the Young's modulus of glass and reduce the refractive index of glass. In the glass of this embodiment, the content of Al2O3 is preferably 0.1 to 20%. If the content of Al2O3 is above 0.1%, its effect can be fully obtained. If it is below 20%, it is not easy to cause problems such as devitrification of glass, increase in reflectivity, and generation of stray light due to reflected light.

[0054] It is more preferably 0.1 to 18%, further preferably 0.1 to 15%, still further preferably 0.1 to 13%, and most preferably 0.1 to 11%.

[0055] From the perspective of vitrifying glass containing Yb without losing transparency, the ratio of the total content of Al2O3, GeO2, Ga2O3, and P2O5 to the total content of SiO2 and B2O3, i.e., (the total content of Al2O3, GeO2, Ga2O3 and P2O5) / (the total content of SiO2 and B2O3), is preferably less than 0.1.

[0056] The glass of this embodiment may contain alkali metal oxides, alkaline earth metal oxides, Sb 2 O 3 , Cl, F, and other components within a range that does not impair the purpose of the present invention.

[0057] When the glass of this embodiment is used for a filter, it is preferable to reduce the reflectivity of the glass in order to prevent stray light caused by reflected light on the glass surface. The reflectivity of the glass depends on the refractive index, and the refractive index at a wavelength of 588 nm is usually preferably 1.700 to 1.900.

[0058] The glass of this embodiment, for example, is used for an optical filter having a function of selectively transmitting specific near-infrared light in addition to having a near-infrared cutoff filter function of transmitting visible light and faithfully reproducing an image based on the visible light, i.e., a so-called dual-bandpass filter, and its thickness is usually mostly less than 3 mm. From the viewpoint of lightweight components, the thickness is preferably less than 2 mm, more preferably less than 1 mm, further preferably less than 0.5 mm, and further preferably less than 0.3 mm. In addition, from the viewpoint of ensuring the strength of the glass, the thickness is preferably more than 0.05 mm.

[0059] When the glass of this embodiment is used as a filter for removing stray light caused by light having a wavelength of about 940 nm, the thickness is preferably less than 10 mm, more preferably less than 7 mm, further preferably less than 4 mm, and further preferably less than 2 mm from the viewpoint of reducing the weight of the component. In addition, from the viewpoint of ensuring the strength of the glass, the thickness is preferably greater than 0.1 mm.

[0060] In the above description, the preferred spectral characteristics of the glass of this embodiment when the thickness is 0.4 mm are described. Therefore, comparison with glass having a thickness other than 0.4 mm can be achieved by converting the spectral characteristics of the glass to a thickness of 0.4 mm.

[0061] The glass according to the present embodiment can be produced, for example, as follows.

[0062] First, the raw materials are weighed and mixed to achieve the above composition range (mixing step). The raw material mixture is placed in a platinum crucible and heated and melted in an electric furnace at a temperature of 1200-1650°C (melting step). After being fully stirred and clarified, it is poured into a mold, cut, and ground to form a flat plate of a specified thickness (forming step).

[0063] In the melting step of the manufacturing method, the highest temperature of the glass during the glass melting is preferably below 1650°C. If the highest temperature of the glass during the glass melting is below the above temperature, problems such as crystallization of the glass and generation of unmelted foreign matter in the glass are less likely to occur. The above temperature is more preferably below 1625°C, and further preferably below 1600°C.

[0064] If the temperature in the melting step is too low, devitrification may occur during melting or melting may take time, so the temperature is preferably 1300° C. or higher, more preferably 1350° C. or higher.

[0065] <Optical filters>

[0066] The optical filter of this embodiment preferably includes the glass of this embodiment.

[0067] The optical filter of this embodiment may also have an optical multilayer film on at least one main surface of the glass of this embodiment. Examples of the optical multilayer film include an IR cut-off film (a film reflecting near infrared rays), a UV / IR cut-off film (a film reflecting ultraviolet rays and near infrared rays), a UV cut-off film (a film reflecting ultraviolet rays), an anti-reflection film, etc. These optical multilayer films may be formed by stacking a plurality of dielectric films by a known method such as a vapor deposition method or a sputtering method.

[0068] A close-fitting strengthening film can also be provided between the glass and the optical multilayer film of the present embodiment. By providing a close-fitting strengthening film, the close-fitting property of the glass and the optical multilayer film can be improved, and film peeling can be suppressed. As the material forming the close-fitting strengthening film, silicon oxide (SiO2), titanium oxide (TiO2), lanthanum titanate (La2Ti2O7), aluminum oxide (Al2O3), a mixture of aluminum oxide and zirconium oxide (ZrO2), magnesium fluoride (MgF2), calcium fluoride (CaF2), strontium fluoride (SrF2), silicon fluoride, etc. can be exemplified. If it is a material comprising fluorine or oxygen, the close-fitting property is high, and the close-fitting property of magnesium fluoride and / or titanium oxide with glass or optical multilayer film is improved, so it is preferred as a close-fitting strengthening film. The close-fitting strengthening film can be a single layer, or it can be more than 2 layers. In the case of more than 2 layers, multiple substances can be combined.

[0069] The optical filter of this embodiment may include an absorption layer on at least one main surface of the glass of this embodiment, and the absorption layer includes a near-infrared absorption pigment having a maximum absorption wavelength in the near-infrared region. By adopting such a structure, an optical filter with a lower transmittance of light in the near-infrared region can be obtained.

[0070] As the near-infrared absorbing dye, a near-infrared absorbing dye composed of at least one selected from the group consisting of a squarylium dye, a phthalocyanine dye, a cyanine dye, and a diimide dye can be preferably used.

[0071] The absorption layer preferably contains a near-infrared absorbing pigment and a transparent resin. The transparent resin is preferably selected from at least one of acrylic resin, epoxy resin, ene thiol resin, polycarbonate resin, polyether resin, polyarylate resin, polysulfone resin, polyether sulfone resin, polyparaphenylene resin, polyarylether phosphine oxide resin, polyimide resin, polyamide-imide resin, polyolefin resin, cyclic olefin resin and polyester resin.

[0072] <Optical Devices>

[0073] The glass of this embodiment can be applied to optical devices. Optical devices are devices that use light to record and transmit information. Examples of optical devices include imaging devices of digital cameras, optical sensors that detect light and convert it into electrical signals, and the like. By applying the glass of this embodiment to optical devices, since the absorption characteristics in the near-infrared region are particularly excellent, it has the advantage of contributing to the miniaturization and thinning of optical devices.

[0074] When the glass of this embodiment is applied to an optical device, it can be used in combination with an optical filter having light absorption characteristics different from those of the glass of this embodiment. Examples of the light absorption characteristics of the optical filter include characteristics having absorption capabilities in a wavelength range different from that of the glass of this embodiment, characteristics having different absorption capabilities in the same near-infrared wavelength range as that of the glass of this embodiment, and the like. By combining the glass of this embodiment with an optical filter having different light absorption characteristics and applying them to an optical device, optical characteristics that are difficult to obtain with a single glass can be obtained. Examples of the optical filter include an infrared cutoff filter disposed near the imaging element of an imaging device, a cover glass covering the opening on the subject side of an optical device, and a lens disposed inside an optical device. In addition, the glass of this embodiment and the optical filter can also be used in a stacked manner.

[0075] As described above, this specification discloses the following glasses and the like.

[0076] [1] Glass containing ytterbium and having a transmittance of 30% or less for light having a wavelength of 940 nm when converted to a thickness of 0.4 mm.

[0077] [2] The glass according to [1], wherein the transmittance of light at a wavelength of 850 nm is 78% or more when converted to a thickness of 0.4 mm.

[0078] [3] The glass according to [1] or [2], wherein the wavelength on the long wavelength side of the wavelengths at which the transmittance is 50% in the wavelength range of 800 to 1100 nm when converted to a thickness of 0.4 mm is λ IRL50 , set the wavelength on the short wavelength side to λ IRS50 When IRL50 With λ IRS50 The absolute value of the difference Δλ IR50 It is 100~160nm.

[0079] [4] The glass according to any one of [1] to [3], wherein the Young's modulus is 100 to 150 GPa.

[0080] [5] The glass according to any one of [1] to [4], which contains 20 mol % or more of Yb2O3, expressed as mol % based on oxide.

[0081] [6] The glass as described in any one of [1] to [5], which contains, expressed as mol% based on oxides, 0.1 to 50 mol% of SiO2, 15 to 40 mol% of B2O3, 0 to 15 mol% of P2O5 and 20 to 60 mol% of Yb2O3.

[0082] [7] The glass as described in any one of [1] to [6], which contains, expressed as mol% based on oxides, 0.1 to 50 mol% of SiO2, 15 to 40 mol% of B2O3, 4 to 10 mol% of P2O5 and 20 to 60 mol% of Yb2O3.

[0083] [8] The glass as described in any one of [1] to [7], which contains 20 to 60 mol % of Yb2O3 and 0 to 7 mol % of ZrO2, expressed as mol % based on oxides.

[0084] [9] The glass as described in any one of [1] to [8], which contains 20 to 60 mol % of Yb2O3 and 65 mol % or more of SiO2 and B2O3 in total, expressed as mol % based on oxides.

[0085]

[10] The glass as described in any one of [1] to [9], which contains 20 to 60 mol % of Yb2O3, expressed as mol % based on oxide, and (the total content of Al2O3, GeO2, Ga2O3 and P2O5) / (the total content of SiO2 and B2O3) is less than 0.1.

[0086]

[11] The glass as described in any one of [1] to

[10] , which contains more than 40 mol % of Yb2O3, expressed as mol % based on oxide.

[0087]

[12] The glass as described in any one of [1] to

[11] , which contains 20 to 60 mol % of Yb2O3 and 0.1 to 20 mol % of La2O3, expressed as mol % based on oxides.

[0088]

[13] The glass according to any one of [1] to

[12] , which contains 20 to 60 mol % of Yb2O3 and 0.1 to 20 mol % of Al2O3, expressed as mol % based on oxides.

[0089]

[14] The glass according to any one of [1] to

[13] , wherein the thickness of the glass is greater than or equal to 0.1 mm and less than 10 mm.

[0090]

[15] The glass according to any one of [1] to

[14] , wherein the glass is used for an optical filter.

[0091]

[16] An optical filter comprising the glass according to any one of [1] to

[15] .

[0092]

[17] An optical device comprising the glass described in any one of [1] to

[14] .

[0093]

[18] An optical device comprising the glass according to any one of [1] to

[14] and an optical filter having optical absorption characteristics different from those of the glass.

[0094] Example

[0095] Hereinafter, although Examples are described, the present invention is not limited to these Examples.

[0096] In addition, the transmittance of the glass is calculated by converting the transmittance at a thickness of 0.4 mm using the following formula (1) based on the measured transmittance at an incident angle of 0 degrees of a glass sample of a specified thickness, assuming that the reflectances of the front and rear surfaces of the glass are 8.12% respectively. In formula (1), R is 0.0812 based on the above reflectance.

[0097] Converted transmittance (thickness 0.4mm) = 100 × (1-R) 2 ×{Measured transmittance (0deg) / (100×(1-R) 2 )} (0.4 / 实测厚度) Formula (1)

[0098] [Glass Preparation]

[0099] For these glasses, the raw materials were weighed and mixed to achieve the compositions (mol% of oxides) shown in Tables 1 to 11, and put into a crucible with an internal volume of about 400cc, and melted at 1400 to 1650°C for 2 hours in an air atmosphere. Then, the glass was clarified and stirred, poured into a rectangular mold of 100mm long×50mm wide×20mm high preheated to about 300°C to 500°C, slowly cooled to room temperature at -1°C / min, cut into a predetermined thickness in the range of 100mm long×50mm wide×0.3 to 1.5mm thick, and optically polished on both sides to obtain a plate-shaped glass plate.

[0100] In addition, the following materials were used as raw materials of each glass.

[0101] SiO2: Oxide

[0102] B2O3: one or more selected from oxides, PBO4 and H3BO3

[0103] P2O5: Any one or more of H3PO4 and PBO4

[0104] GeO2: Oxide

[0105] ZrO2: Oxide

[0106] Ga2O3: Oxide

[0107] Yb2O3: oxide

[0108] La2O3: Oxide

[0109] Al2O3: any one or more of oxide and Al(OH)3

[0110] In addition, the raw materials of glass are not limited to the above materials, and known materials may be used.

[0111] [evaluate]

[0112] For each glass plate prepared as above, the transmittance at a wavelength of 300 to 1200 nm (incident angle 0 degrees) was measured using a spectrophotometer (manufactured by JASCO Corporation, V-570), and converted to the transmittance at a thickness of 0.4 mm using the above formula (1). Based on the converted transmittance, the transmittance of light at a wavelength of 940 nm, the transmittance of light at a wavelength of 850 nm, and the transmittance of light at a wavelength of 400 nm were obtained. In addition, based on the transmittance measured above, within the range of wavelengths of 870 nm to 910 nm and 990 to 1030 nm, the transmittance data of each 1 nm of wavelength from the short wavelength side to the long wavelength side was approximated using a linear equation, and the wavelength at which the transmittance was 50% was calculated based on the obtained approximate formula, and the short wavelength side was λ IRS50 , the long wavelength side is λIRL50 .

[0113] The results of the spectral characteristics are shown in Tables 1 to 11.

[0114] Examples 1 to 5 are comparative examples, and Examples 6 to 100 are embodiments.

[0115] In addition, the transmittance curves of the glasses of Example 7 (Example), Example 90 (Example) and Example 2 (Comparative Example) for light with a wavelength of 300 to 1200 nm are shown in FIG. Figure 1 middle.

[0116] <Young's modulus>

[0117] Some of the glass samples prepared above were measured using an ultrasonic pulse method. The results are shown in Table 12.

[0118] <Refractive Index>

[0119] For some of the glass samples prepared as above, the transmittance and reflectance at incident angles of 0deg and 30deg were measured, and the refractive index at a wavelength of 588nm was calculated according to the method described in "Optical Thin Film Filter Design" by Mitsunobu Kohiyama (Publisher: OPTRONICS, 2006).

[0120] The results are shown in Table 13.

[0121] [Table 1]

[0122] Table 1

[0123] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Example 9 Example 10 <![CDATA[SiO2]]> 3.1 0.0 66.1 48.9 0.0 41.6 32.9 41.6 32.9 32.9 <![CDATA[B2O3]]> 25.2 59.2 0.0 13.5 63.0 24.0 23.2 24.0 23.2 23.2 <![CDATA[P2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Yb2O3]]> 1.5 2.1 10.3 12.8 16.3 19.0 22.8 20.0 23.8 24.8 <![CDATA[GeO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Al203]]> 0.0 8.1 23.6 19.6 8.1 0.0 0.0 0.0 0.0 0.0 <![CDATA[Na2O]]> 0.0 0.0 0.0 3.8 0.0 0.0 0.0 0.0 0.0 0.0 ZnO 27.9 5.1 0.0 0.0 6.7 0.0 0.0 0.0 0.0 0.0 BaO 0.0 4.5 0.0 0.0 1.8 0.0 0.0 0.0 0.0 0.0 <![CDATA[TiO2]]> 3.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[ZrO2]]> 3.5 0.0 0.0 0.0 0.0 0.0 7.3 0.0 7.3 7.3 <![CDATA[WO3]]> 12.9 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 Ga, O3 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[La2O3]]> 12.7 21.1 0.0 0.0 4.1 15.4 13.8 14.4 12.8 11.8 <![CDATA[Gd2O3]]> 0.4 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Nb2O5]]> 5.9 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ta2O5]]> 3.9 0.0 0.0 1.3 0.0 0.0 0.0 0.0 0.0 0.0 total 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 <![CDATA[SiO2+B2O3(mol%)]]> 28.4 59.2 66.1 62.4 63.0 65.6 56.1 65.6 56.1 56.1 <![CDATA[(Al2O3+GeO2+Ga2O3+P2O5) / (SiO2+B2O3)]]> 0.00 0.14 0.36 0.31 0.13 0.00 0.00 0.00 0.00 0.00 Transmittance of light with a wavelength of 940 nm (thickness 0.4 mm) (%) 76.3 74.2 38.2 34.1 30.1 27.7 20.7 26.1 19.1 18.5 Transmittance of light with a wavelength of 850 nm (thickness 0.4 mm) (%) 84.2 84.5 84.0 84.2 84.2 83.2 82.3 83.0 81.8 82.1 Transmittance of light with a wavelength of 400 nm (thickness 0.4 mm) (%) 82.8 84.1 85.5 85.3 85.4 84.1 83.4 84.1 83.5 83.5 <![CDATA[Wavelength λ on the short wavelength side with a transmittance of 50% IRS50 (nm)]]> Undefined Undefined 899.1 901.0 902.7 897.5 892.9 896.8 891.9 891.5 <![CDATA[Wavelength λ on the long wavelength side with a transmittance of 50% IRL50 (nm)]]> Undefined Undefined 971.7 982.4 990.0 994.5 1001.1 996.6 1003.0 1003.4 <![CDATA[λ IRL50 -l RS50 (nm)]]> - - 72.6 81.4 87.2 97.0 108.2 99.8 111.1 111.9

[0124] [Table 2]

[0125] Table 2

[0126] Example 11 Example 12 Example 13 Example 14 Example 15 Example 16 Example 17 Example 18 Example 19 Example 20 <![CDATA[SiO2]]> 32.9 32.9 32.3 32.6 32.9 33.6 32.9 32.9 32.9 32.9 <![CDATA[B2O3]]> 23.2 23.2 22.8 24.0 23.2 23.0 23.2 23.2 23.2 23.2 <![CDATA[P2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Yb2O3]]> 25.8 26.8 26.3 26.5 26.8 26.5 26.8 26.8 26.8 27.8 <![CDATA[GeO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Al2O3]]> 0.0 0.0 2.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Na2O]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 ZnO 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 BaO 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[TiO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[ZrO2]]> 7.3 7.3 7.1 6.2 6.3 7.2 5.3 4.3 3.3 3.3 <![CDATA[WO3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ga2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[La2O3]]> 10.8 9.8 9.6 10.7 10.8 9.7 11.8 12.8 13.8 12.8 <![CDATA[Gd2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Nb2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ta2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 total 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 <![CDATA[SiO2+B2O3(mol%)]]> 56.1 56.1 55.0 56.6 56.1 56.6 56.1 56.1 56.1 56.1 <![CDATA[(Al2O3+GeO2+Ga2O3+P2O5) / (SiO2+B2O3)]]> 0.00 0.00 0.04 0.00 0.00 0.00 0.00 0.00 0.00 0.00 Transmittance of light with a wavelength of 940 nm (thickness 0.4 mm) (%) 17.4 21.8 16.6 16.8 16.7 16.4 16.7 17.8 17.3 16.3 Transmittance of light with a wavelength of 850 nm (thickness 0.4 mm) (%) 81.9 82.3 81.8 81.8 81.9 81.7 81.8 82.0 81.9 81.8 Transmittance of light with a wavelength of 400 nm (thickness 0.4 mm) (%) 83.4 83.4 83.4 83.2 83.5 83.3 83.4 83.5 83.3 83.3 <![CDATA[Wavelength λ on the short-wavelength side with a transmittance of 50% IRS50 (nm)]]> 890.5 893.8 889.9 890.5 890.2 890.0 890.3 891.0 890.6 889.8 <![CDATA[Wavelength λ on the long wavelength side with a transmittance of 50% IRL50 (nm)]]> 1004.6 1000.1 1005.3 1005.5 1005.9 1006.0 1005.7 1004.5 1005.0 1006.0 <![CDATA[λ IRL50 -l IRS50 (nm)]]> 114.1 106.3 115.4 115.0 115.7 116.0 115.4 113.5 114.4 116.2

[0127] [Table 3]

[0128] Table 3

[0129] Example 21 Example 22 Example 23 Example 24 Example 25 Example 26 Example 27 Example 28 Example 29 Example 30 <![CDATA[SiO2]]> 32.9 32.9 32.9 32.9 32.9 32.9 32.9 32.9 32.9 32.9 <![CDATA[B2O3]]> 23.2 23.2 23.2 23.2 23.2 23.2 23.2 29.6 28.7 26.9 <![CDATA[P2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Yb2O3]]> 27.8 28.8 28.8 28.8 22.8 22.8 22.8 22.8 22.8 22.8 <![CDATA[GeO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Al2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Na2O]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 ZnO 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 BaO 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[TiO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[ZrO2]]> 2.3 1.3 0.3 0.0 3.6 1.8 0.9 0.9 1.8 3.6 <![CDATA[WO3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ga2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[La2O3]]> 13.8 13.8 14.8 15.1 17.4 19.3 20.2 13.8 13.8 13.8 <![CDATA[Gd2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Nb2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ta2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 total 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 <![CDATA[SiO2+B2O3(mol%)]]> 56.1 56.1 56.1 56.1 56.1 56.1 56.1 62.5 61.6 59.8 <![CDATA[(Al2O3+GeO2+Ga2O3+P2O5) / (SiO2+B2O3)]]> 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 0.00 Transmittance of light with a wavelength of 940 nm (thickness 0.4 mm) (%) 16.5 15.8 16.7 16.1 20.4 21.3 21.5 21.3 21.2 20.8 Transmittance of light with a wavelength of 850 nm (thickness 0.4 mm) (%) 81.8 81.7 81.8 81.7 82.2 82.2 82.3 82.6 82.5 82.2 Transmittance of light with a wavelength of 400 nm (thickness 0.4 mm) (%) 83.0 83.2 83.0 83.3 83.3 83.1 83.2 83.9 83.8 83.6 <![CDATA[Wavelength λ on the short wavelength side with a transmittance of 50% IRS50 (nm)]]> 890.0 889.7 890.1 889.2 893.2 893.7 893.9 894.5 894.3 893.8 <![CDATA[Wavelength λ on the long wavelength side with a transmittance of 50% IRL50 (nm)]]> 1006.1 1006.6 1005.2 1006.0 1002.2 1001.4 1001.4 1001.5 1001.5 1001.9 <![CDATA[λ IRL50 -l IRS50 (nm)]]> 116.1 116.9 115.0 116.8 109.0 107.7 107.5 107.0 107.2 108.1

[0130] [Table 4]

[0131] Table 4

[0132] Example 31 Example 32 Example 33 Example 34 Example 35 Example 36 Example 37 Example 38 Example 39 Example 40 <![CDATA[SiO2]]> 32.9 32.9 32.9 32.9 15.0 15.0 32.9 32.9 32.9 32.9 <![CDATA[B2O3]]> 23.2 23.2 23.2 23.2 25.0 25.0 23.2 23.2 23.2 23.2 <![CDATA[P2O5]]> 0.0 0.0 0.0 0.0 5.0 5.0 3.6 5.5 6.4 0.0 <![CDATA[Yb2O3]]> 29.3 29.8 30.3 30.8 35.0 40.0 22.8 22.8 22.8 22.8 <![CDATA[GeO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Al2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Na2O]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 ZnO 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 BaO 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[TiO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[ZrO2]]> 0.3 0.3 0.3 0.3 0.0 0.0 3.6 1.8 0.9 3.6 <![CDATA[WO3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ga2O3]]> 0.0 0.0 0.0 0.0 20.0 15.0 0.0 0.0 0.0 3.6 <![CDATA[La2O3]]> 14.3 13.8 13.3 12.8 0.0 0.0 13.8 13.8 13.8 13.8 <![CDATA[Gd2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Nb2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ta2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 OD 0.0 0.0 0.0 total 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 <![CDATA[SiO2+B2O3(mol%)]]> 56.1 56.1 56.1 56.1 40.0 40.0 56.1 56.1 56.1 56.1 <![CDATA[(Al2O3+GeO2+Ga2O3+P2O5) / (SiO2+B2O3)]]> 0.00 0.00 0.00 0.00 0.63 0.50 0.06 0.10 0.11 0.06 Transmittance of light with a wavelength of 940 nm (thickness 0.4 mm) (%) 14.1 13.4 12.4 12.9 10.3 7.5 21.3 21.8 21.5 20.4 Transmittance of light with a wavelength of 850 nm (thickness 0.4 mm) (%) 81.8 81.9 81.6 81.8 81.9 81.3 82.6 83.4 83.7 82.2 Transmittance of light with a wavelength of 400 nm (thickness 0.4 mm) (%) 82.8 83.0 82.9 83.2 83.6 83.2 83.4 83.8 84.7 83.1 <![CDATA[Wavelength λ on the short wavelength side with a transmittance of 50% IRS50 (nm)]]> 889.1 888.6 887.8 888.1 886.2 883.5 894.2. 894.6 894.5 893.1 <![CDATA[Wavelength λ on the long wavelength side with a transmittance of 50% IRL5C (nm)]]> 1006.9 1001.3 1008.3 1001.9 1009.1 1011.9 1000.4 999.4 999.1 1001.8 <![CDATA[λ IRL5O -l IRS50 (nm)]]> 117.8 118.8 120.4 119.8 122.9 128.4 106.3 104.8 105.2 108.7

[0133] [Table 5]

[0134] Table 5

[0135] Example 41 Example 42 Example 43 Example 44 Example 45 Example 46 Example 47 Example 48 Example 49 Example 50 <![CDATA[SiO2]]> 32.9 32.9 32.9 32.9 32.9 32.9 32.9 32.3 31.6 14.7 <![CDATA[B2O3]]> 23.2 23.2 23.2 23.2 23.2 23.2 23.2 22.8 22.3 24.5 <![CDATA[P2O5]]> 0.0 2.0 4.0 0.0 0.0 0.0 0.0 2.0 1.9 4.9 <![CDATA[Yb2O3]]> 22.8 30.3 30.3 30.3 30.3 30.3 30.3 31.7 33.0 41.2 <![CDATA[GeO2]]> 0.0 0.0 0.0 0.0 0.0 2.0 4.0 0.0 0.0 0.0 <![CDATA[Al2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Na2O]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 ZnO 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 BaO 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[TiO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[ZrO2]]> 1.8 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.0 <![CDATA[WO3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ga2O3]]> 5.5 0.0 0.0 2.0 4.0 0.0 0.0 0.0 0.0 14.7 <![CDATA[La2O3]]> 13.8 11.3 9.3 11.3 9.3 11.3 9.3 11.1 10.9 0.0 <![CDATA[Gd2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Nb2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ta2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 total 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 <![CDATA[SiO2+B2O3(mol%)]]> 56.1 56.1 56.1 56.1 56.1 56.1 56.1 55.0 54.0 39.2 <![CDATA[(Al2O3+GeO2+Ga2O3+P2O5) / (SiO2+B2O3)]]> 0.10 0.04 0.07 0.04 0.07 0.04 0.07 0.04 0.04 0.50 Transmittance of light with a wavelength of 940 nm (thickness 0.4 mm) (%) 22.0 14.1 13.4 12.9 12.4 12.7 13.2 12.9 11.4 7.7 Transmittance of light with a wavelength of 850 nm (thickness 0.4 mm) (%) 81.2 82.4 82.5 82.1 82.2 81.8 82.0 82.1 81.6 80.9 Transmittance of light with a wavelength of 400 nm (thickness 0.4 mm) (%) 80.8 83.5 83.8 83.3 83.4 83.0 83.5 83.4 82.9 83.2 <![CDATA[Wavelength λ on the short wavelength side with a transmittance of 50% IRS50 (nm)]]> 894.1 889.1 888.9 888.3 887.9 888.3 888.7 888.1 886.7 883.3 <![CDATA[Wavelength λ on the long wavelength side with a transmittance of 50.5 IRL50 (nm)]]> 1000.4 1006.1 1006.6 1007.4 1007.8 1007.8 1007.3 1007.1 1008.6 1011.5 <![CDATA[λ IRL50 -l IRS50 (nm)]]> 106.3 117.0 117.7 119.1 119.9 119.6 118.6 119.0 121.9 128.2

[0136] [Table 6]

[0137] Table 6

[0138] Example 51 Example 52 Example 53 Example 54 Example 55 Example 56 Example 57 Example 58 Example 59 Example 60 <![CDATA[SiO2]]> 14.4 30.3 29.7 13.0 11.0 14.3 14.2 13.0 11.0 28.3 <![CDATA[B2O3]]> 24.0 22.8 22.3 25.0 25.0 23.8 23.6 25.0 25.0 22.8 <![CDATA[P2O5]]> 4.8 3.9 3.8 5.0 5.0 4.8 4.7 5.0 5.0 5.9 <![CDATA[Yb2O3]]> 42.3 31.7 33.0 42.0 44.0 42.9 43.4 42.0 44.0 31.7 <![CDATA[GeO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Al2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Na2O]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 ZnO 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 BaO 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[TiO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[ZrO2]]> 0.0 0.3 0.3 0.0 0.0 0.0 0.0 0.0 0.0 0.3 <![CDATA[WO3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ga2O3]]> 14.4 0.0 0.0 15.0 15.0 14.3 14.2 7.5 7.5 0.0 <![CDATA[La2O3]]> 0.0 11.1 10.9 0.0 0.0 0.0 0.0 7.5 7.5 11.1 <![CDATA[Gd2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Nb2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ta2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 total 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 <![CDATA[SiO2+B2O3(mol%)]]> 38.5 53.1 52.0 38.0 36.0 38.1 37.7 38.0 36.0 51.1 <![CDATA[(Al2O3+GeO2+Ga2O3+P2O5) / (SiO2+B2O3)]]> 0.50 0.07 0.07 0.53 0.56 0.50 0.50 0.33 0.35 0.12 Transmittance of light with a wavelength of 940 nm (thickness 0.4 mm) (%) 7.1 11.4 11.5 7.2 6.0 6.3 6.3 6.9 6.4 11.5 Transmittance of light with a wavelength of 850 nm (thickness 0.4 mm) (%) 80.7 81.5 81.7 80.7 80.1 80.5 79.4 80.0 79.8 81.7 Transmittance of light with a wavelength of 400 nm (thickness 0.4 mm) (%) 83.0 83.2 83.1 83.1 82.6 83.1 81.9 82.4 82.3 83.1 <![CDATA[Wavelength λ on the short-wavelength side with a transmittance of 50% IRS50 (nm)]]> 882.3 886.7 886.6 882.6 880.9 881.1 879.2 880.7 879.3 886.8 <![CDATA[Wavelength λ on the long wavelength side with a transmittance of 50% IRL50 (nm)]]> 1012.2 1008.0 1007.9 1012.1 1013.5 1013.1 1013.2 1012.5 1013.1 1008.0 <![CDATA[λ IRL50 -A IRS50 (nm)]]> 129.8 121.4 121.3 129.4 132.7 132.0 134.0 131.8 133.8 121.3

[0139] [Table 7]

[0140] Table 7

[0141] Example 61 Example 62 Example 63 Example 64 Example 65 Example 66 Example 67 Example 68 Example 69 Example 70 <![CDATA[SiO2]]> 27.8 13.0 11.0 12.5 10.6 12.5 10.6 15.0 15.0 15.0 <![CDATA[B2O3]]> 22.3 25.0 25.0 24.0 24.0 24.0 24.0 25.0 25.0 25.0 <![CDATA[P2O5]]> 5.8 5.0 5.0 4.8 4.8 4.8 4.8 5.0 5.0 7.0 <![CDATA[Yb2O3]]> 33.0 42.0 44.0 44.2 46.2 44.2 46.2 40.0 40.0 35.0 <![CDATA[GeO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Al2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 18.0 <![CDATA[Na2O]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 ZnO 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 BaO 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[TiO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[ZrO2]]> 0.3 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[WO3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ga2O3]]> 0.0 3.8 3.8 7.2 7.2 14.4 14.4 7.5 3.8 0.0 <![CDATA[La2O3]]> 10.9 11.3 11.3 7.2 7.2 0.0 0.0 7.5 11.3 0.0 <![CDATA[Gd2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Nb2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ta2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 total 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 <![CDATA[SiO2+B2O3(mol%)]]> 50.1 38.0 36.0 36.5 34.6 36.5 34.6 40.0 40.0 40.0 <![CDATA[(Al2O3+GeO2+Ga2O3+P2O5) / (SiO2+B2O3)]]> 0.12 0.23 0.24 0.33 0.35 0.53 0.56 0.31 0.22 0.63 Transmittance of light with a wavelength of 940 nm (thickness 0.4 mm) (%) 11.7 7.3 6.4 6.3 5.6 6.0 5.5 7.6 8.2 11.8 Transmittance of light with a wavelength of 850 nm (thickness 0.4 mm) (%) 82.0 79.5 79.1 79.7 79.0 80.0 79.7 80.4 80.2 82.4 Transmittance of light with a wavelength of 400 nm (thickness 0.4 mm) (%) 83.5 81.8 81.6 82.4 81.9 82.6 82.5 82.0 82.3 84.4 <![CDATA[Wavelength λ on the short wavelength side with a transmittance of 50% IRS50 (nm)]]> 887.0 880.1 877.8 878.7 877.4 880.1 879.3 881.8 881.8 885.9 <![CDATA[Wavelength λ on the long wavelength side with a transmittance of 50% IRL50 (nm)]]> 1007.9 1012.0 1013.0 1013.2 1014.2 1013.7 1014.3 1011.7 1011.1 1006.8 <![CDATA[λ IRL50 -l IRS50 (nm)]]> 120.9 131.9 135.2 134.5 136.9 133.7 135.0 129.9 129.3 120.9

[0142] [Table 8]

[0143] Table 8

[0144] Example 71 Example 72 Example 73 Example 74 Example 75 Example 76 Example 77 Example 78 Example 79 Example 80 <![CDATA[SiO2]]> 15.0 15.0 15.0 13.0 13.0 15.0 13.0 11.0 26.8 25.9 <![CDATA[B2O3]]> 25.0 25.0 25.0 25.0 25,0 25.0 25.0 25.0 22.3 22.3 <![CDATA[P2O5]]> 7.0 5.0 5.0 7.0 7.0 5.0 7.0 9.0 5.8 5.8 <![CDATA[Yb2O3]]> 40.0 35.0 40.0 35.0 40.0 40.0 40.0 40.0 33.9 34.9 <![CDATA[GeO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Al2O3]]> 13.0 20.0 15.0 20.0 15.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Na2O]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 ZnO 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 BaO 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[TiO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[ZrO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.3 0.3 <![CDATA[WO3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ga2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[La2O3]]> 0.0 0.0 0.0 0.0 0.0 15.0 15.0 15.0 10.9 10.9 <![CDATA[Gd2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Nb2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ta2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 total 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 <![CDATA[SiO2+B2O3(mol%)]]> 40.0 40.0 40.0 38.0 38.0 40.0 38.0 36.0 49.2 48.2 <![CDATA[(Al2O3+GeO2+Ga2O3+P2O5) / (SiO2+B2O3)]]> 0.50 0.63 0.50 0.71 0.58 0.13 0.18 0.25 0.12 0.12 Transmittance of light with a wavelength of 940 nm (thickness 0.4 mm) (%) 8.4 10.3 8.4 11.3 8.9 8.2 8.0 8.4 11.0 10.9 Transmittance of light with a wavelength of 850 nm (thickness 0.4 mm) (%) 81.5 82.2 81.8 82.7 81.9 79.4 79.3 79.9 81.6 81.5 Transmittance of light with a wavelength of 400 nm (thickness 0.4 mm) (%) 83.8 84.4 84.1 84.5 84.2 81.8 81.8 82.3 83.2 83.1 <![CDATA[Wavelength λ on the short-wavelength side with a transmittance of 50% IRS50 (nm)]]> 882.7 884.3 882.5 885.2 882.8 879.7 879.1 879.0 886.0 886.0 <![CDATA[Wavelength λ on the long-wavelength side with a transmittance of 50% IRL50 (nm)]]> 1010.1 1007.9 1010.1 1006.7 1009.4 1010.7 1010.8 1010.4 1008.6 1008.7 <![CDATA[λ IRL50 -l IRS50 (nm)]]> 127.4 123.6 127.6 121.5 126.6 131.0 131.7 130.8 122.6 122.7

[0145] [Table 9]

[0146] Table 9

[0147] Example 81 Example 82 Example 83 Example 84 Example 85 Example 86 Example 87 Example 88 Example 89 Example 90 <![CDATA[SiO2]]> 24.9 15.0 15.0 15.0 9.6 8.7 7.7 9.4 8.5 7.5 <![CDATA[B2O3]]> 22.3 24.0 23.0 22.0 24.0 24.0 24.0 23.6 23.6 23.6 <![CDATA[P2O5]]> 5.8 6.0 7.0 8.0 5.8 6.7 7.7 5.7 6.6 7.5 <![CDATA[Yb2O3]]> 35.9 40.0 40.0 40.0 46.2 46.2 46.2 47.2 47.2 47.2 <![CDATA[GeO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Al2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Na2O]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 ZnO 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 BaO 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[TiO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[ZrO2]]> 0.3 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[WO3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ga2O3]]> 0.0 0.0 0.0 0.0 14.4 14.4 14.4 14.2 14.2 14.2 <![CDATA[La2O3]]> 10.9 15.0 15.0 15.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Gd2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Nb2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ta2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 0.0 total 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 100.0 <![CDATA[SiO2+B2O3(mol%)]]> 47.2 39.0 38.0 37.0 33.7 32.7 31.7 33.0 32.1 31.1 <![CDATA[(Al2O3+GeO2+Ga2O3+P2O5) / (SiO2+B2O3)]]> 0.12 0.15 0.18 0.22 0.60 0.65 0.70 0.60 0.65 0.70 Transmittance of light with a wavelength of 940 nm (thickness 0.4 mm) (%) 10.0 7.9 8.2 8.4 6.0 5.6 5.8 5.2 5.0 5.1 Transmittance of light with a wavelength of 850 nm (thickness 0.4 mm) (%) 81.0 79.1 79.2 79.4 79.6 79.5 79.9 79.6 79.6 79.6 Transmittance of light with a wavelength of 400 nm (thickness 0.4 mm) (%) 82.8 81.5 81.7 81.8 82.3 82.3 82.7 82.8 83.1 82.9 <![CDATA[Wavelength λ on the short wavelength side with a transmittance of 50% IRS50 (nm)]]> 884.4 878.5 878.7 878.7 879.4 879.4 879.7 878.7 878.4 878.7 <![CDATA[Wavelength λ on the long wavelength side with a transmittance of 50% IRL50 (nm)]]> 1009.0 1010.7 1010.4 1010.0 1013.3 1013.7 1013.5 1014.5 1014.8 1014.5 <![CDATA[λ IRL50 -l IRS50 (nm)]]> 124.6 132.2 131.7 131.3 133.9 134.3 133.8 135.8 136.4 135.8

[0148] [Table 10]

[0149] Table 10

[0150] Example 91 Example 92 Example 93 Example 94 Example 95 Example 96 <![CDATA[SiO2]]> 10.0 9.0 8.0 14.0 13.0 12.0 <![CDATA[B2O3]]> 25.0 25.0 25.0 26.0 27.0 28.0 <![CDATA[P2O5]]> 10.0 11.0 12.0 5.0 5.0 5.0 <![CDATA[Yb2O3]]> 40.0 40.0 40.0 40.0 40.0 40.0 <![CDATA[GeO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Al2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Na2O]]> 0.0 0.0 0.0 0.0 0.0 0.0 ZnO 0.0 0.0 0.0 0.0 0.0 0.0 BaO 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[TiO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[ZrO2]]> 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[WO3]]> 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ga2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[La2O3]]> 15.0 15.0 15.0 15.0 15.0 15.0 <![CDATA[Gd2O3]]> 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Nb2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 <![CDATA[Ta2O5]]> 0.0 0.0 0.0 0.0 0.0 0.0 total 100.0 100.0 100.0 100.0 100.0 100.0 <![CDATA[SiO2+B2O3(mol%)]]> 35.0 34.0 33.0 40.0 40.0 40.0 <![CDATA[(Al2O3+GeO2+Ga2O3+P2O5) / (SiO2+B2O3)]]> 0.29 0.32 0.36 0.13 0.13 0.13 Transmittance of light with a wavelength of 940 nm (thickness 0.4 mm) (%) 8.2 8.8 9.0 8.0 8.0 8.0 Transmittance of light with a wavelength of 850 nm (thickness 0.4 mm) (%) 79.9 79.8 79.9 79.6 79.6 79.8 Transmittance of light with a wavelength of 400 nm (thickness 0.4 mm) (%) 82.5 82.1 82.1 81.8 81.9 81.9 <![CDATA[Wavelength λ on the short wavelength side with a transmittance of 50% IRS50 (nm)]]> 880.1 880.4 880.6 879.3 879.6 879.8 <![CDATA[Wavelength λ on the long wavelength side with a transmittance of 50% IRL50 (nm)]]> 1010.6 1009.8 1009.6 1010.9 1011.0 1011.0 <![CDATA[λ IRL50 -l IRS50 (nm)]]> 130.5 129.4 129.0 131.6 131.4 131.2

[0151] [Table 11]

[0152] Table 11

[0153] Example 97 Example 98 Example 99 Example 100 <![CDATA[SiO2]]> 7.4 7.3 7.1 6.9 <![CDATA[B2O3]]> 23.1 22.7 22.3 21.6 <![CDATA[P2O5]]> 7.4 7.3 7.1 6.9 <![CDATA[Yb2O3]]> 48.1 49.1 50.0 51.7 <![CDATA[GeO2]]> 0.0 0.0 0.0 0.0 <![CDATA[Al2O3]]> 0.0 0.0 0.0 0.0 <![CDATA[Na2O]]> 0.0 0.0 0.0 0.0 ZnO 0.0 0.0 0.0 0.0 BaO 0.0 0.0 0.0 0.0 <![CDATA[TiO2]]> 0.0 0.0 0.0 0.0 <![CDATA[ZrO2]]> 0.0 0.0 0.0 0.0 <![CDATA[WO3]]> 0.0 0.0 0.0 0.0 <![CDATA[Ga2O3]]> 9.7 9.5 9.4 9.1 <![CDATA[La2O3]]> 4.2 4.1 4.0 3.9 <![CDATA[Gd2O3]]> 0.0 0.0 0.0 0.0 <![CDATA[Nb2O5]]> 0.0 0.0 0.0 0.0 <![CDATA[Ta2O5]]> 0.0 0.0 0.0 0.0 total 100.0 100.0 100.0 100.0 <![CDATA[SiO2+B2O3(mol%)]]> 30.6 30.0 29.5 28.4 <![CDATA[(Al2O3+GeO2+Ga2O3+P2O5) / (SiO2+B2O3)]]> 0.56 0.56 0.56 0.56 Transmittance of light with a wavelength of 940 nm (thickness 0.4 mm) (%) 4.9 4.4 4.3 3.8 Transmittance of light with a wavelength of 850 nm (thickness 0.4 mm) (%) 78.9 78.6 78.2 77.8 Transmittance of light with a wavelength of 400 nm (thickness 0.4 mm) (%) 81.5 81.2 81.1 80.9 <![CDATA[Wavelength λ on the short wavelength side with a transmittance of 50% IRS50 (nm)]]> 879.2 878.1 877.7 876.3 <![CDATA[Wavelength λ on the long wavelength side with a transmittance of 50% IRL50 (nm)]]> 1016.6 1017.3 1017.4 1018.1 <![CDATA[λ IRL50 -l IRS50 (nm)]]> 130.5 129.4 129.0 131.2

[0154] [Table 12]

[0155] Table 12

[0156] Young's modulus(GPa) Example 6 117.4 Example 7 131.6 Example 35 123.8 Example 36 124.7 Example 58 125.3 Example 67 130.6 Example 68 124.5 Example 69 124.7 Example 72 122.9 Example 73 130.4 Example 76 123.9 Example 78 115.1 Example 81 121.0 Example 90 130.5

[0157] [Table 13]

[0158] Table 13

[0159] Refractive Index Example 35 1.795 Example 36 1.804 Example 72 1.754 Example 73 1.773

[0160] The above results show that the transmittance of the glasses of Examples 6 to 100 at a wavelength of 940 nm is 30% or less when converted to a thickness of 0.4 mm, and that the glasses are excellent in shielding properties against near-infrared light.

[0161] The present invention has been described in detail or with reference to specific embodiments, but it is obvious to those skilled in the art that various changes and modifications may be made without departing from the spirit and scope of the present invention. This application is based on Japanese patent application (Japanese Patent Application No. 2022-104803) filed on June 29, 2022, and its contents are incorporated herein by reference.

[0162] Possibility of industrial application

[0163] The glass of the embodiment of the present invention has excellent absorption characteristics of specific near-infrared light and can be used for optical filters of imaging devices such as cameras and sensors for transport aircraft, which have been increasingly improved in recent years.

Claims

1. A glass containing ytterbium, wherein the transmittance of light having a wavelength of 940 nm is 30% or less when the thickness is converted to 0.4 mm.

2. The glass according to claim 1, wherein: When converted to a thickness of 0.4 mm, the transmittance of light with a wavelength of 850 nm is 78% or more.

3. The glass according to claim 1, wherein: When converted to a thickness of 0.4 mm, the wavelength on the long wavelength side of the wavelength where the transmittance is 50% in the wavelength range of 800 to 1100 nm is defined as λ. IRL50 , set the wavelength on the short wavelength side to λ IRS50 When IRL50 With λ IRS50 The absolute value of the difference Δλ IR50 It is 100~160nm.

4. The glass according to claim 1, wherein: Young's modulus is 100-150 GPa.

5. The glass according to claim 1, wherein: Expressed as mol % based on oxide, it contains 20 mol % or more of Yb2O3.

6. The glass according to claim 1, wherein: Expressed as mol% based on oxides, it contains 0.1 to 50 mol% of SiO2, 15 to 40 mol% of B2O3, 0 to 15 mol% of P2O5 and 20 to 60 mol% of Yb2O3.

7. The glass according to claim 1, wherein: Expressed as mol% based on oxides, it contains 0.1 to 50 mol% of SiO2, 15 to 40 mol% of B2O3, 4 to 10 mol% of P2O5 and 20 to 60 mol% of Yb2O3.

8. The glass according to claim 1, wherein: Expressed as mol% based on oxides, it contains 20 to 60 mol% of Yb2O3 and 0 to 7 mol% of ZrO2.

9. The glass according to claim 1, wherein: Expressed as mol % based on oxides, it contains 20 to 60 mol % of Yb2O3 and more than 65 mol % of SiO2 and B2O3 in total.

10. The glass according to claim 1, wherein: Expressed as mol% based on oxides, it contains 20 to 60 mol% Yb2O3, and (the total content of Al2O3, GeO2, Ga2O3 and P2O5) / (the total content of SiO2 and B2O3) is less than 0.

1.

11. The glass according to claim 1, wherein: Expressed as mol % on an oxide basis, it contains more than 40 mol % of Yb2O3.

12. The glass according to claim 1, wherein: Expressed as mol% based on oxides, it contains 20 to 60 mol% of Yb2O3 and 0.1 to 20 mol% of La2O3.

13. The glass according to claim 1, wherein: Expressed as mol% based on oxides, it contains 20 to 60 mol% of Yb2O3 and 0.1 to 20 mol% of Al2O3.

14. The glass according to claim 1, wherein: The thickness of the glass is greater than 0.1 mm and less than 10 mm.

15. The glass according to claim 1, wherein: The glass is used for optical filters. 16 . An optical filter comprising the glass according to claim 1 .

17. An optical device comprising the glass according to any one of claims 1 to 14.

18. An optical device comprising the glass according to any one of claims 1 to 14 and an optical filter having an optical absorption characteristic different from that of the glass.

Citation Information

Patent Citations

  • Semiconductor device

    JP2022104803A

  • Glass, glass material for press molding, optical element blank, and optical element

    WO2016114274A1